Geometrias de poder e espacialidades da produção científica da geografia brasileira de 1998 a 2018 - (:unkn) unknown (Universidade Estadual de Ponta Grossa, 2022)
This study seeks to comprehend how power-geometries implicated within the Brazilian geographic scientific production spatialities in the period between 1998 and 2018. Initially developed by Massey (1991), the power-geometries concept refers to the different potentials of human action through space-time, articulated in multiple and dynamic scalar arrangements of political, economic, cultural and epistemic relationships. An intrinsic part in this interaction entanglement, the Brazilian geographic scientific field (BORDIEU, 2004) was reshaped at the end of the 1990’s with the rise of digital means of results transmission and the new science evaluation and financing politics in the country. The increasing federal public investment between 2005 and 2015 allowed geography postgraduate programs to be installed in the five regions of Brazil. However, these scientific production spatialities present different capacities on mobilizing material and symbolic resources as a result of the unequal structure and articulation of their trajectories, as the survey conducted on the development agencies and programs’ websites data bases showed. Throughout the consultation of the metadata set established with 20,865 articles from 97 magazines stored on the Brazilian Geography Observatory (Observatório da Geografia Brasileira – OGB) by the Territory Study Group (Grupo de Estudos Territoriais – GETE UEPG), we verified that the centrality of the southeastern institutions, principally in the state of São Paulo, is a result of the larger intellectual production in online journals with higher academic valuation as well. Through the OGB archive treatment, via computational tools operations proposed by Silva and Silva (2016) and Social Network Analysis (SNA) (HIGGINS; RIBEIRO, 2018), the hierarchy and proximity relations in between the concepts, themes and authors were demonstrated. By building 19,220 meta-connected key-words networks, we demonstrated the increasingly centrality of the concept of territory and the consistency of the urban geography studies in the last two decades. The relatively new expansion of the pluriversity noticed in the field reports to studies on management, development, biomes, health, teaching, gender, tourism, socio-environmental conflicts and geo technologies. Whereas in the articulated networks, in the period of 2013-2019, among 48,922 Qualis A1 and A2 categories publication references, the hypercentrality of Milton Santos is expressive. With a legacy that keeps gathering more scientific capital when mobilized in the comprehension process of multiple phenomena in different geographic realities, the importance and relevancy of Milton’s thoughts challenges for a greater plurality of approaches in our field.
Keywords: Poder; Epistemologia da Geografia; Cientometria; Pós-graduação; Power; Geographical Epistemology; Scientometrics; Post-graduation; CNPQ::CIENCIAS EXATAS E DA TERRA::GEOCIENCIAS